FACTORS INFLUENCING OIL PALM FARMERS’ FRESH FRUIT BUNCHES MARKETING DECISIONS THROUGH COLLECTORS IN RUKAM VILLAGE - Dinda Aulia; Evahelda (UIN Sunan Gunung Djati Bandung, 2026)
The marketing of fresh fruit bunches of oil palm is an important part of the agribusiness supply chain. The main problem in fresh fruit bunches marketing is farmers’ dependence on collectors. This study aims to analyze the decision-making patterns of oil palm farmers in choosing marketing channels and to analyze the factors that influence oil palm farmers’ decisions to sell fresh fruit bunches through collectors. This study employs a quantitative approach using a survey of 50 oil palm farmers in Rukam Village, Mendo Barat Subdistrict. Respondents were selected through purposive sampling based on the fresh fruit bunches marketing channels they utilized. This study uses descriptive analysis to describe the characteristics of the respondents and the decision-making patterns of farmers in choosing fresh fruit bunches marketing channels, as well as binary logistic regression analysis to examine the influence of each independent variable on the probability of farmers’ decisions in choosing marketing channels. The results of the study indicate that the marketing patterns for fresh fruit bunches among smallholder oil palm farmers are still dominated by sales through collectors. Social relationships emerged as the most influential factor affecting farmers’ decisions to sell their fresh fruit bunches through collectors in Rukam Village, Mendo Barat Subdistrict. These findings reinforce the perspective that smallholder oil palm farmers’ decisions regarding the marketing of their fresh fruit bunches are not entirely determined by economic factors and physical access, but are also influenced by the social relationships formed within local marketing networks.